Pulmonary Hypertension, Mortality, and Cardiovascular Disease in CKD and ESRD Patients: A Systematic Review and Meta-analysis - Tang, Mengyao; Batty, Jonathan A.; Lin, Chiayu; Fan, Xiaohong; Chan, Kevin E.; Kalim, Sahir (American journal of kidney diseases, 2018)
Pulmonary hypertension is common in patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) and may be associated with poor outcomes. The magnitude of the association between pulmonary hypertension and mortality is uncertain due to the small size and variable findings of observational studies. Systematic review and meta-analysis of observational studies using subgroup analyses and metaregression. Patients with ESRD or earlier stages of CKD. Observational studies reporting clinical outcomes in patients with co-existing pulmonary hypertension and CKD or ESRD identified using a systematic search of PubMed and Embase. Pulmonary hypertension diagnosed by Doppler echocardiography. All-cause mortality, cardiovascular mortality, and cardiovascular events. 16 studies, with 7,112 patients with an overall pulmonary hypertension prevalence of 23%, were included. Pulmonary hypertension was associated with increased risk for all-cause mortality among patients with CKD (relative risk [RR], 1.44; 95% CI, 1.17-1.76), with ESRD receiving maintenance dialysis (RR, 2.32; 95% CI, 1.91-2.83), and with a functioning kidney transplant (RR, 2.08; 95% CI, 1.35-3.20). Pulmonary hypertension was associated with increased risk for cardiovascular events in patients with CKD (RR, 1.67; 95% CI, 1.07-2.60) and ESRD receiving dialysis (RR, 2.33; 95% CI, 1.76-3.08). There was an association between pulmonary hypertension and increased risk for cardiovascular mortality in patients with CKD or ESRD (RR, 2.20; 95% CI, 1.53-3.15). Heterogeneity of included studies, possibility of residual confounding, unavailability of individual patient-level data, and possibility of outcome reporting bias. Pulmonary hypertension is associated with a substantially increased risk for death and cardiovascular events in patients with CKD and ESRD. Risk is higher in patients with ESRD receiving dialysis compared with patients with CKD stages 1 to 5. Understanding the effect of interventions to lower pulmonary artery pressure on the survival of these patents awaits their evaluation in randomized controlled trials.